Chinese terms of address for Jews from the Tang to the Qing dynasty - Li, Dawei (Journal of Jewish studies, 2020)
The earliest documentation of Jews entering ancient China has been shown to be in the Tang dynasty. From then to the Yuan, Ming and Qing dynasties, the terms of address for the Jewish communities recorded in Chinese historical documents surface in different ways, among which Shíhū, Shùhū, Gŭjiào, Tiānzhú Jiào, Lánmào Huíhui, Tiăojīn Jiào, Rúdéyà and so on had been the most influential until Yóutài was coined by Karl Friedlich Gutzlaff in 1833. The conventions for addressing Jews fall into two categories, transliteration and meaning-based translation. The former is indicated by such diverse terms as Shíhū, Shùhū, Yóutài and their homophones. The latter is mainly shown by the ways in which Kāifēng Jews were addressed. Historical study of the terms of address for Jews deepens our understanding of the interactions between the Jewish and the Chinese civilizations.